Adaptation, implementation, and pilot testing of a school - based mental health literacy program in Cambodia - Phoeun, Bunna (Đại học Quốc gia Hà Nội, 2020)
Background : School - based MHL programs may offer an effective and sustainable approach to promote teacher and student mental health literacy . Although programs developed elsewhere may require substantial adaptation for different cultural and institutional contexts, working from regionally adapted materials may alleviate this burden. This paper will describe adaptation and pilot testing of a school - based MHL program in Cambodia, using materials previously adapted for Vietnam (The Guide - VN). Few additional adaptations were required . Observers recorded satisfactory fidelity , noting that skill in implementation varied between teachers . Pre - post analysis of 67 teachers and 275 students showed significant post - test differences in teacher knowledge , attitudes , and beliefs , all favouring the intervention ( p < .001 ) . Significant differences in student knowledge and attitude scores also favoured the intervention group ( p < .001 ) , although effect sizes were smaller. Findings from this pilot RCT support the potential benefits of school - based MHL training in Cambodia , where existing mental health resources are limited . Use of materials adapted for Vietnam reduced the adaptation burden ; however , small to moderate effect sizes suggest opportunities for further adaptation , refinement, and testing of the curriculum to optimize impact. This includes developing additional implementation strategies and support for Cambodian teachers